Dairy Cows Experimentally Infected With Bovine Leukemia Virus Showed an Increased Milk Production in Lactation Numbers 3–4: A 4-Year Longitudinal Study - Yang, Yi; Gong, Zaicheng; Lu, Yi; Lu, Xubin; Zhang, Jilei; Meng, Ye; Peng, Yalan; Chu, Shuangfeng; Cao, Wenqiang; Hao, Xiaoli; Sun, Jie; Wang, Heng; et al. (Frontiers in Microbiology, 2022)
Bovine leukemia virus (BLV) is widespread in global cattle populations, but the effects of its infection on milk quantity and quality have not been clearly elucidated in animal models. In this study, 30 healthy first-lactation cows were selected from ≈2,988 cows in a BLV-free farm with the same criteria of parity, age, lactation number, as well as milk yield, SCS, and composition (fat, protein, and lactose). Subsequently, these cows were randomly assigned to the intervention (n = 15) or control (n = 15) group, and reared in different cowsheds. Cows in the intervention group were inoculated with 1 × phosphate-buffered solution (PBS) resuspended in peripheral blood mononuclear cells (PBMC) from a BLV-positive cow, while the controls were inoculated with the inactivated PBMC from the same individual. From June 2016 to July 2021, milk weight (kg) was automatically recorded by milk sensors, and milk SCS and composition were originated from monthly performed dairy herd improvement (DHI) testing. Fluorescence resonance energy transfer (FRET)–qPCR and ELISA showed that cows in the intervention group were successfully infected with BLV, while cows in the control group were free of BLV for the entire period. At 45 days post-inoculation (DPI), the numbers of whole blood cells (WBCs) (P = 0.010), lymphocytes (LYMs) (P = 0.002), and monocytes (MNCs) (P = 0.001) and the expression levels of IFN-γ (P = 0.013), IL-10 (P = 0.031), and IL-12p70 (P = 0.008) increased significantly in the BLV infected cows compared to the non-infected. In lactation numbers 2–4, the intervention group had significantly higher overall milk yield (P < 0.001), fat (P = 0.031), and protein (P = 0.050) than the control group, while milk SCS (P = 0.038) and lactose (P = 0.036) decreased significantly. Further analysis indicated that BLV infection was associated with increased milk yield at each lactation stage in lactation numbers 3–4 (P = 0.021 or P < 0.001), but not with SCS and milk composition. Together, this 4-year longitudinal study revealed that artificial inoculation of BLV increased the milk yield in cows in this BLV challenge model.